2020
DOI: 10.3390/su12166605
|View full text |Cite
|
Sign up to set email alerts
|

Parents as Agents: Engaging Children in Environmental Literacy in China

Abstract: China, one of the most polluting countries in the world, is facing tremendous challenges in dealing with environmental problems. Although the government has implemented various regulations and introduced strong enforcement to reduce toxic emissions and encourage recycling, little is known about how parents in China socialise their children into environmentally responsible individuals. This article reports on what 267 Chinese parents do, as agents of environmental protection, to raise their children’s awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
12
1
1
Order By: Relevance
“…It was found that there is a strong correlation between environmental literacy level and the attitude of individuals [64]. The attitude of someone would help to make eco-friendly environmental behaviors in the long run.…”
Section: The Attitude and Behavior Of The Undergraduates Towards The ...mentioning
confidence: 99%
“…It was found that there is a strong correlation between environmental literacy level and the attitude of individuals [64]. The attitude of someone would help to make eco-friendly environmental behaviors in the long run.…”
Section: The Attitude and Behavior Of The Undergraduates Towards The ...mentioning
confidence: 99%
“…This may be because those who have held responsibilities as parents have better exemplary values to teach to their children than singles. Parents play an important role in the agentive socialisation role in their engagement with children on pro-environmentalism (Iwaniec & Curdt-Christiansen, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering this condition, this result is analogous to the research [39] which revealed that students with low-income parents tend to have better habits or behavior towards the environment. In addition, students with low socioeconomic status tend to have higher environmental literacy and vice versa [40]. However, this does not happen to farmers and freelancers, even though both types of work have a small income compared to other occupations.…”
Section: The Influence Of Parents' Occupation On Ekmentioning
confidence: 97%